ROLE OF THE VERHOVNA RADA IN POLITICAL PROCESSES OF UKRAINE (2013-2015) - K. G. Ilinova (Проблемы постсоветского пространства, 2017)
In article the role of the Verkhovna Rada in political processes which happened in Ukraine since November, 2013 is considered. The main attention is paid to research of a position of the Ukrainian parliament on domestic and foreign policy.